Union-Management Welfare Plans - Rosenthal, Robert J. (Quarterly Journal of Economics, 1947)
I. The trend toward plans: Gompers' attitude, 64; reasons for late development, 65; growth of current plans, 68. — II. Structure and characteristics of the plans: number in operation, 72; neglect of actuarial considerations, 73; methods of financing, 75; types of administration, 77; benefits and coverage, 80. — III. Implications and prospects: their function as stopgaps, 86; influence of union bargaining power and industrial stability, 87; relation to more comprehensive programs, 93.